Redistribution, selection, and trade - Miriam Kohl (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
This paper examines the distributional effects of international trade in a general equilibrium model with heterogeneous agents and a welfare state redistributing income. The redistribution scheme is financed by a progressive income tax and gives the same absolute transfer to all individuals. Ceteris paribus, international trade leads to an increase in income per capita but also to higher income inequality on two fronts. Inter-group inequality between managers and workers increases, and intra-group inequality within the group of managers goes up as well. We show that for constant tax rates, there is an endogenous increase in the size of the welfare state that works against the increase in inequality, yet cannot offset it. The paper also sheds light on the conditions under which trade can actually lead to a Pareto improvement.
urn:nbn:de:bsz:14-qucosa-229489
Keywords: D31; F12; F16; H24; H25; 330; International trade; Income inequality; Redistribution; Heterogeneous firms